Airway Hygiene Nursing Care Is Not Effective with Drinking Warm Water Therapy - Muhaimin, Ahmad; Sholehah, Baitus (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Pulmonary edema is a common complication in chronic and acute kidney failure which has signs and symptoms, namely shortness of breath due to hypoxia caused by a buildup of fluid in the alveoli (pulmonary edema) which can cause ineffective airway clearance. The purpose of writing this scientific work is to study and implement the nursing care process for ineffective airway clearance with warm drinking water therapy for CKD patients in the ICCU room. The research design uses case studies on two of Mr. W and Mrs. T. Nursing care is carried out using the nursing process which includes assessment, data analysis, nursing diagnosis, nursing planning, implementation and evaluation. The results of nursing care for 3 x 24 hours showed that client 1 looked quite good, not short of breath, the secret was able to come out quite a lot and was thick, the RR was 26 x/min. Meanwhile, client 2 also looks quite good, it's not tight, the secret can come out quite a lot and the RR is thick at 26 x/min. The results of the evaluation carried out, the problem of ineffective airway clearance was resolved on the third day for both participants. Implementation by recommending giving warm drinking water more frequently can help patients loosen their breathing so that secretions can come out and reduce the patient's breathing frequency.